2008
DOI: 10.1007/s11094-008-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Complexes Based on 4-aryl-2-hydroxy-4-oxo-2-butenoic Acid N-heterylamides

Abstract: Reaction of 4-aryl-2-hydroxy-4-oxo-2-butenoic acid N-hetarylamides with copper, zinc, and cadmium dichlorides led to the formation of bis[3-aryl-1-(N-hetaryl)carboxamido-1,3-propanedionato]copper, -zinc, and -cadmium, respectively. Compounds with high antimicrobial activity were found among these products. 3890091-150X/08/4207-0389

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Thermogravimetric studies indicated that the N-heterylamides I coordinated to the metals as bidentate O-O ligands. IR spectra of V -VII also confirmed their structures and agreed with the literature properties of chelate complexes II -IV [6,7].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Thermogravimetric studies indicated that the N-heterylamides I coordinated to the metals as bidentate O-O ligands. IR spectra of V -VII also confirmed their structures and agreed with the literature properties of chelate complexes II -IV [6,7].…”
supporting
confidence: 84%
“…We prepared previously complexes of copper, zinc, and cadmium with N-heterylamides of 4-aryl-2-hydroxy-4-oxo-2-butenoic acids (I) [6,7]. High antimicrobial activity was observed for the products II -IV (Scheme).…”
mentioning
confidence: 99%
“…1 H NMR spectra were registered on a Bruker AM-300 spectrometer (300 MHz) in DMSO-d 6 , internal reference TMS. IR spectra were recorded on a Specord M-80 spectrometer from KBr pellets.…”
mentioning
confidence: 99%
“…These polyfunctional reagents show high reactivity due to the presence of several reaction sites in their structure [1,2]. They can act as C-nucleophiles and carbonyl electrophiles in the reactions, being promising starting materials for the synthesis of a variety of acyclic and heterocyclic compounds [1][2][3][4].…”
mentioning
confidence: 99%